Implementasi Manajemen Konflik Terhadap Perilaku Bullying Di Pondok Pesantren Al-Fattah, Jember - Ananda, Dahniar; Nur, Lailiyah; Rifa’i, Samsul; Zuhro’ Fitriana, Ani Qotuz (CV. ITTC INDONESIA, 2023)
Bullying behavior in the pesantren environment can create an environment that is less supportive of the development of students. Bullying behavior can hurt students, so they feel unwanted and rejected by their environment. This of course will have an effect on the various activities of Islamic boarding school students. The researcher took the title